Membangun Kinerja Usaha Melalui Faktor Pembentuk Kapabilitas Pelaku Kewirausahaan Industri Kreatif Nasional - Iwan Hermawan; VS Tripriyo PS (Jurnal Ekonomi dan Bisnis, 2015)
One of national creative industry roadmap key aspect is the character capability of businessmen. This research aims to empirically define the factors forming the entrepreneurial capabilities of creative industries and its impact on business performance. Art and creative technology industries in three cities in Indonesia, including Denpasar, Jogjakarta and Surakarta are used as samples. The factor analysis is employed to define the presence of three factors-which forming capabilities of national entrepreneurial creative industries, including: (1) internal management-risk management, (2) independence and anti-plagiarism design, and (3) the unique design and renewable idea. The statistic test finds the significant influence of entrepreneurial capabilities of creative industries on business performance. While internal management-risk management is the dominant factor contributing the business performance. Some other findings are national entrepreneurs have understood that the concept, idea, and knowledge were the main capital to accelerate the national creative economy. The entrepreneurs also understand the importance of self-reliance and anti-plagiarism design. But on the other hand, the majority of them have dominant of the external locus of control.